The hidden significance of urban agriculture - Mougeot, Luc J. A. (International Food Policy Research Institute, 2000)
"Urban agriculture—agriculture located within or on the fringe of a town or city—may be one way to bolster city food supplies while also increasing the incomes of the poor. Urban agriculture uses resources, products, and services found in and around the urban area and, in turn, often supplies resources, products, and services to that area. Urban agricultural systems include horticulture, floriculture, forestry, aquaculture, and livestock production... To improve urban agriculture and make it more sustainable, farmers must use better practices and governments must promote or better manage it through more informed policies. Nongovernmental organizations (NGOs) can support these efforts." -- from Text